ANALISIS PELAKSANAAN KAS KECIL (PETTY CASH) PADA PT DELI JAYA SAMUDERA - Bonifasius Hamonangan Tambunan; Jhon Feliks Simanjuntak (Journal of Economic and Business, 2021)
This research is a qualitative descriptive research with data collection methods used are interviews, documentation, and observation. The interview method was carried out by conducting questions and answers with related parties and related to the implementation of petty cash. The documentation method is a data collection technique that is carried out by researching, collecting, and analyzing company documents. The observation method is carried out directly on the company by collecting data related to the implementation of petty cash recording. The results showed that in the implementation of petty cash at PT. Deli Jaya Samudera is carried out using the fixed fund method. However, replenishment of petty cash funds is carried out when the petty cash balance is depleted without waiting until the end of the period to be replenished which is not in accordance with the method used. And in the implementation of petty cash, the company treasurer also holds a petty cash fund which can make the company treasurer work more.